Values of Character Education in the Sirih Pinang Symbol: A Cultural Value of Coastal Society - Daryanti, Fitri; Jazuli, Muhammad; Florentinus, Totok Sumaryanto; Hartono, Hartono (Jurnal Pendidikan Progresif, 2020)
Values of Character Education in the Sirih Pinang Symbol in the Nyambai Tradition of Saibatin Customary Community on the West Coast. Objective: This research aims to reveal the values of character education contained in the symbol of Sirih Pinang when the people of Lampung on the coast held a Nyambai tradition. Method: This research is a qualitative descriptive study, data collection techniques are conducted through observation, interviews, and documentation studies. Data analysis is done by reducing, display, drawing conclusions and verification. Findings: The results found that sirih pinang in a nyambai event used by the community as a symbol that regulates the behavior of the community. The use of sirih pinang in a nyambai event contains the values of character education that teaches about the value of unity, the value of respect, the value of togetherness, the value of friendship, mutual assistance and the value of tolerance that should be inherited to the young generation. Conclusion: Sirih Pinang in a nyambai event can be used as a guide line of knowledge for children in the conduct and behaviour in the daily life of both in the family, school, and in the community.Keywords: values, character education, sirih pinang, nyambai tradition, indigenous event.DOI: 10.23960/jpp.v10.i2.202013